People's Republic of China-Macao Special Administrative Region : 2019 Article IV Consultation Discussions-Press Release; Staff Report; and Statement by the Executive Director for Macao SAR. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2019)
This 2019 Article IV Consultation highlights that while more moderate than in the past, gaming and tourism revenue in Macao Special Administrative Region picked up as the economy returned to expansion since mid-2016. Progress with diversification towards mass-gaming and nongaming tourism, together with the continued China gaming monopoly, are expected to deliver growth of around 4 percent in the medium term. Risks are tilted to the downside, mainly emanating from Mainland China. Prudent macroeconomic policies and high reserves provide strong buffers against shocks. In addition to supporting diversification, fulfilling social needs, and maintaining macroeconomic stability, the policies priorities explained in the report will reduce external imbalances. The report also discusses that the current housing macroprudential stance and related fiscal measures appear broadly appropriate. A broader set of policies are advised to support housing affordability, where continued efforts to boost housing supply will be key.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet